Pemasaran bagi Petualang sebagai Kegiatan Komunikasi Pemasaran - Ratih Tresnati (MediaTor (Jurnal Komunikasi), 2006)
Marketing for Adventurer aims adventurer as its consumers. Instead of revenue-based, adventurer consumer is based on lifestyle. Their hobbies are outdoor sports such as bungee jumping, rock climbing, off-road driving, wild-river canoeing, etc. Marketing for adventurer has specific strategic: (1) STP Strategy—market segmenting, market targeting, market positioning; (2) Customer Experience Strategy (CES) as the sequel of Experiential Marketing (EM). EM focuses more on emotion touch and feelings.